Does the Carbon Emission Trading Policy Promote Foreign Direct Investment?: A Quasi-Experiment From China - Shao, Wei; Yu, Xiaobo; Chen, Ziqi (Frontiers in Environmental Science, 2022)
As an important policy to promote global energy transition and carbon emission reduction, does the carbon emission trading policy help to promote foreign direct investment inflows, thus alleviating the contradiction between environment and economic development? Based on the “OLI Paradigm”, by using the data of 30 China’s provinces from 2007 to 2016 and taking China’s pilot implementation carbon emission transaction policy in 2013 as the natural experiment, so as to construct a differences-in-differences model, this paper empirically analyzed the impact of carbon emission transaction policies on foreign direct investment, and conducted an analysis and discussion on related heterogeneity in depth. The empirical results show that: (1) There is a positive correlation between carbon emission trading policy and foreign direct investment; (2) The results of heterogeneity analysis show that, the effect of carbon emission trading policy on the increase of FDI is more significant in the areas with a stronger environmental regulation, a higher degree of marketization and low energy consumption. The conclusions of this paper enrich the analysis of the effectiveness of government environmental policies from the perspective of both environment and economic development, and provide relevant policy enlightenment for developing countries in environmental regulation and attracting foreign direct investment.